(3GdWHbGJ GdSfjI aj JQGLe GdMfajIs - (3Jbj GdOjf Hf YHO GdbGOQ GdJejej GdZRj,J (B1010 (3g` s
(3ChdgG (B:s
(3ef GdMSf Hf YKeGf s
(3BNQgG (B:s
(3Ydi Hf eMeO Hf EHQGgje s
(3QJHJ GdGSeGA Ydi GdMQhas
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B91s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B312 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B169 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1099s
Keywords: (3GdJGQjNs